PowerPoint® Presentation Flaws and Failures: A Psychological Analysis - Kosslyn, Stephen M.; Kievit, Rogier A.; Russell, Alexandra G.; Shephard, Jennifer M. (Frontiers in Psychology, 2012)
Electronic slideshow presentations are often faulted anecdotally, but little empirical work has documented their faults. Three studies reported here document psychological causes of their flaws. In Study 1 we found that eight psychological principles are often violated in PowerPoint® presentations, across different fields—for example, academic research presentations generally were no better or worse than business presentations. In Study 2 we found that respondents reported having noticed, and having been annoyed by, specific problems in presentations arising from violations of particular psychological principles. Finally, in Study 3 we showed that observers are not highly accurate in recognizing when slides violated a specific psychological rule. Furthermore, even when they correctly identified the violation, they often could not explain the nature of the problem. In sum, the psychological foundations for effective slideshow presentation design are neither obvious nor necessarily intuitive, and presentation designers in all fields, from education to business to government, could benefit from explicit instruction in relevant aspects of psychology.